PENGARUH KOMPOSISI MEDIA TANAM ORGANIK ARANG SEKAM DAN PUPUK PADAT KOTORAN SAPI DENGAN TANAH TIMBUNAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP TANAMAN KANGKUNG DARAT (Ipomea reptans Poir) - Trya Juniyati; Asmah Adam; Patang Patang (Jurnal Pendidikan Teknologi Pertanian, 2016)
This research aim to determine the effect of composition variations of the organic plants media husk charcoal and cow’s faces solid manure with embankment soil and production of kale plants and composition ratio of organic husk charcoal and cow’s faces solid manure with soil embankment to the growth and viability of upland kale plants. This research use a completely randomized design with 4 treatments and 4 replicates are P0 : soil embankment (control), P1: soil embankment , husks charcoal, cow’s faces solid manure (1:1:2), P2: soil embankment, husks charcoal, cow’s faces solid manure (1:1:3) and P3: soil embankment, husks charcoal, cow’s faces solid manure (1:1:1). Variables that have been observed consist of the production, growth and viability. Analysis of data used by analysis of variance. The result showed the treatment has a real effect to the production of kale upland plants that is located in P2 treatment with the composition of soil embankment, husks charcoal, cow’s faces solid manure (1:1:3) with wet weight average perpolybag spread 26.625 grams. The highest growth lies in P1 treatment with the composition of the soil embankment, husks charcoal, cow’s faces solid manure (1:1:2) with an average equal to 27.725cm, while the best composition tha very influential to viability in value of 100% is P2 treatmentwith the value 100% viability